Pengaruh Kesadaran Wajib Pajak dan Modernisasi Administrasi Perpajakan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Moh. Fikri Fauzi; Elly Halimatusadiah (Bandung Conference Series: Accountancy, 2022)
Abstract. Taxes have a big contribution to development in Indonesia because taxes are state revenues. Compliance with paying motor vehicle taxes is very important to increase local revenue. The purpose of this study was to determine the effect of taxpayer awareness and modernization of tax administration on motor vehicle taxpayer compliance at the Pajajaran SAMSAT Office in Bandung City. This study uses a verification method with a quantitative approach. Data collection techniques used were questionnaires with 50 motor vehicle taxpayers registered at the SAMSAT Pajajaran office in Bandung. The object of this research is taxpayer awareness, tax administration modernization, and motor vehicle taxpayer compliance. The data used in this study using primary data obtained from the results of filling out questionnaires by respondents of motorized vehicle taxpayers registered at the SAMSAT Pajajaran office in Bandung City. The statistical technique used in data analysis is multiple regression method with SPSS version 23 application. Based on the analysis, it is known that taxpayer awareness, tax administration modernization, and taxpayer compliance at the SAMSAT Pajajaran Office, Bandung City have been going well. Mandatory awareness and compliance of motor vehicle taxpayers in the "Very Good" criteria and administrative modernization in the "good" criteria. The results of the study indicate that taxpayer awareness has an effect on Motor Vehicle Taxpayer Compliance at the Pajajaran SAMSAT Office in Bandung City and Tax Administration Modernization has no Effect on Motor Vehicle Taxpayer Compliance at the Pajajaran SAMSAT Office in Bandung City. Abstrak. Pajak memiliki kontribusi yang besar terhadap pembangunan di Indonesia karena pajak merupakan penerimaan negara. Kepatuhan membayar pajak kendaraan bermotor menjadi hal yang sangat penting untuk meningkatkan pendapatan asli daerah. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dari kesadaran wajib pajak dan modernisasi administrasi perpajakan terhadap kepatuhan wajib pajak kendaraan bermotor di Kantor SAMSAT Pajajaran di Kota Bandung. Penelitian ini menggunakan metode verifikatif dengan pendekatan kuantitatif. Teknik pengumpulan data yang digunakan dengan menggunakan kuesioner dengan responden sebanyak 50 wajib pajak kendaraan bermotor yang terdaftar di Kantor SAMSAT Pajajaran di Kota Bandung. Objek pada penelitian ini adalah kesadaran wajib pajak, modernisasi administrasi perpajakan, dan kepatuhan wajib pajak kendaraan bermotor. Data yang digunakan dalam penelitian ini menggunakan data primer yang diperoleh dari hasil pengisian kuesioner oleh responden wajib pajak kendaraan bermotor yang terdaftar di kantor SAMSAT Pajajaran di Kota Bandung. Teknik statistik yang digunakan dalam analisis data adalah metode regresi berganda dengan aplikasi SPSS versi 23. Hasil penelitian menunjukkan bahwa Kesadaran Wajib Pajak berpengaruh positif signifikan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kantor SAMSAT Pajajaran di Kota Bandung dan Modernisasi Administrasi Perpajakan tidak Berpengaruh terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kantor SAMSAT Pajajaran di Kota Bandung.